2023
DOI: 10.3390/su15129371
|View full text |Cite
|
Sign up to set email alerts
|

How Can Collective Action Support the Agroecological Transition in Geographical Indication Vineyards? Insights from the Loire Valley Wine Area

Abstract: Few studies have examined the agroecological transition in viticulture, which involves transformation processes, especially at the territorial scale where collective action plays a key role in the dissemination of transition strategies. Collective action in the agroecological transition must be studied in order to encourage and accelerate changes in practices. In this study, collective action is analyzed to understand how governance structures influence the development of collective agroecological transition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Given its bottom-up and polycentric character, the GI system has itself been described as a sustainable policy instrument [22]. Indeed, empirical studies have highlighted the potential of GIs to contribute to different dimensions of sustainability [23][24][25][26]. However, some cases, including some of the most notorious GI "success stories" have shown that introducing GIs can also negatively affect various sustainability dimensions in the respective areas [19,27,28].…”
Section: Geographical Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its bottom-up and polycentric character, the GI system has itself been described as a sustainable policy instrument [22]. Indeed, empirical studies have highlighted the potential of GIs to contribute to different dimensions of sustainability [23][24][25][26]. However, some cases, including some of the most notorious GI "success stories" have shown that introducing GIs can also negatively affect various sustainability dimensions in the respective areas [19,27,28].…”
Section: Geographical Indicationsmentioning
confidence: 99%
“…Given the bottom-up nature of GIs in a polycentric governance framework, the theoretical work of Elinor Ostrom seems to provide a fitting analytical framework [24,25,35]. In particular, the empirically derived "design principles" for collective choice arrangements provide an intuitive yet comprehensive framework to analyse situations where stakeholders themselves develop institutional arrangements to overcome common challenges.…”
Section: Ostrom's Design Principlesmentioning
confidence: 99%
“…In response to these challenges, alternatives based on the principles of agroecology have emerged in recent years, which are based on ecological principles and biological interactions in agrosystems, with the aim of making agricultural processes sustainable. This includes pest control, appropriate fertilization, and environmental protection in all dimensions [34,35].…”
Section: Introductionmentioning
confidence: 99%